2023
DOI: 10.2147/idr.s391349
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Features and Impact of High Glucose Level on Virulence Gene Expression and Serum Resistance of Klebsiella pneumoniae Causing Liver Abscess in Diabetic Patients

Abstract: Purpose Klebsiella pneumoniae ( K. pneumoniae ) is a Gram-negative bacterium that is predominantly associated with liver abscesses in global diabetic patients. High levels of glucose in the surrounding of K. pneumonia increase its pathogenicity including capsular polysaccharide (CPS) and fimbriae. Other important virulent factors include outer membrane protein A (ompA) and regulator mucoid phenotype A (rmpA). The objective of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…The underlying biological mechanisms may include tissue hyperglycemia and a predilection for certain microorganisms. 2,7,8 Previous research studies have shown that DM impairs the innate and adaptive immune system, impairing macrophages, T cells, neutrophils, and NK cells. This immune dysfunction increases the risk of infection including liver abscess.…”
Section: Discussionmentioning
confidence: 99%
“…The underlying biological mechanisms may include tissue hyperglycemia and a predilection for certain microorganisms. 2,7,8 Previous research studies have shown that DM impairs the innate and adaptive immune system, impairing macrophages, T cells, neutrophils, and NK cells. This immune dysfunction increases the risk of infection including liver abscess.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, this upregulation contributes to enhanced resistance against the immune system via the cAMP signaling pathway. 14 These observational studies provide preliminary evidence on potential exposure factors associated with bacterial pneumonia in individuals with diabetes. In previous observational studies, the presence of reverse causality has posed a challenge, rendering it arduous to ascertain a causal association between bacterial pneumonia and diabetes.…”
Section: Introductionmentioning
confidence: 91%
“…It has been reported that carbapenem-resistant hypervirulent Klebsiella pneumoniae (CR-hvKP) has caused fatal hospital infection. 3 And hyperglycemia increases the gene expression of RmpA and ompA in hvKP through cAMP signaling pathway, 4 which will increase the cost of treatment and extend the length of hospital stay.…”
Section: Dear Editormentioning
confidence: 99%